The effect of the initial distribution of labor-related property rights on the allocative efficiency of labor markets - Dietl, Helmut M.; Lang, Markus; Orlowski, Johannes; Wegelin, Philipp (Frontiers in Behavioral Economics, 2024)
We conduct an empirical study to examine the impact of the initial distribution of labor-related property rights on the allocative efficiency of labor markets for skilled workers in a highly competitive labor market (professional basketball). Specifically, we compare a regime where employers can trade workers to other employers without the worker's consent to one where workers have the right to negotiate freely with other employers and move without their employer's consent (free agents). Our findings indicate a decline in productivity among workers who transition to new employers as free agents, a trend not observed among non-free agents. This observation suggests that allocative efficiency may be higher when workers are traded without their consent than when they exercise their autonomy as free agents. These results point to a significant influence of the initial distribution of labor-related property rights on the efficiency of labor markets, potentially challenging the Coase Theorem. However, the absence of a statistically significant difference in productivity changes between free agents and non-free agents moving to new employers prevents a definitive rejection of the Coase Theorem’s predictions.